A Solution Approach on Reducing Defects in Batik Tanah Liek Production Process of a Small and Medium-sized Enterprise - Agus Sutanto; Nilda Tri Putri; Tessa Alqifti; Sha'ri Mohd Yusof (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2024)
Small and medium enterprises (SMEs) often struggle with implementing eﬀective quality management practices, especially in traditional industries like batik production. These challenges include ensuring consistent product quality to diﬀerentiate from competitors and attract customers. This study focuses on addressing quality control issues in small-scale Batik Tanah Liek production, where signiﬁcant defects persist. The research aims to assess existing practices, identify defect causes, and propose solutions to enhance product quality and reduce rejection rates. These eﬀorts contribute to improving production eﬃciency and supporting the sustainability of this traditional craft. The study employs a systematic approach combining quality management methodologies, including data collection, problem identiﬁcation, brainstorming, the Failure Mode and Eﬀects Analysis (FMEA) approach, and actionable recommendations. Data was gathered through a questionnaire to capture perspectives on defects and quality control issues in batik production. Key quality challenges identiﬁed include faded batik, torn fabric, and incorrect motifs. Analysis revealed that the primary cause of incorrect motifs is the malfunctioning canting tool, which hinders proper wax application. Additionally, defects in dyeing and boiling processes contribute to fabric fading and tearing, exacerbating quality issues. The ﬁndings underscore the need for systematic solutions, such as creating clear work instructions, designing Standard Operating Procedures (SOPs) for process consistency, and implementing preventive maintenance schedules for equipment. By addressing these issues, the study provides practical interventions to improve production quality. These measures not only enhance the economic viability of SMEs but also play a crucial role in preserving the cultural heritage of Batik Tanah Liek. The implications of this research highlight the potential for broader adoption of quality management practices in traditional industries to ensure their sustainability in competitive markets.